As melopéias para flauta de César Guerra-Peixe: um estudo interpretativo - Diogo Artur Bianco Navia (2012)
The main goal of this paper is discussing compositional and interpretive aspects of César Guerra-Peixes three Melopéias for solo flute. The pieces were written in distinct moments, presenting features that reveal, in part, convictions and questions from three diferente compositional periods. Thus, we provide an analysis based on Guerra-Peixes own composition method: Melos e Harmonia Acústica. By identifying melodic elements, our analysis presents solutions for the interpretive problems posed by each Melopéia.